An investigation of the factors associated with default of scheduled drug pick-ups and clinic visits by patients on antiretroviral therapy at Murchison Hospital, Kwa Zulu Natal Province in South Africa - Zulu, Kahelo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.